2006
DOI: 10.1007/s11145-006-9020-3
|View full text |Cite
|
Sign up to set email alerts
|

Preschool twin study of the relation between attention-deficit/hyperactivity disorder and prereading skills

Abstract: Numerous studies have examined the etiology of the association between reading difficulties and attention-deficit hyperactivity disorder (ADHD) in school-age children, but little is known about the relation between prereading skills and ADHD behaviors prior to the beginning of formal reading instruction. A population-based sample of 809 pairs of preschool twins completed an extensive battery of prereading measures, and the parent of each twin completed an ADHD rating scale. Phenotypic analyses revealed small b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
82
2
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(99 citation statements)
references
References 44 publications
10
82
2
5
Order By: Relevance
“…It is possible that the RSD children had low motivation towards kindergarten literacy-related activities (reflected in the kindergarten teachers' evaluation) and also during individual assessment situations (reflected in the testers' evaluations). However, it is also possible that task avoidance taps self-regulation or inattention that co-exists with reading and spelling disability (e.g., Willcutt et al, 2007). Previous studies have shown links between task avoidance and reading (e.g., Onatsu-Arvilommi & Nurmi, 2000) as well as between task avoidance and spelling (e.g., Georgiou et al, 2010;Liao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the RSD children had low motivation towards kindergarten literacy-related activities (reflected in the kindergarten teachers' evaluation) and also during individual assessment situations (reflected in the testers' evaluations). However, it is also possible that task avoidance taps self-regulation or inattention that co-exists with reading and spelling disability (e.g., Willcutt et al, 2007). Previous studies have shown links between task avoidance and reading (e.g., Onatsu-Arvilommi & Nurmi, 2000) as well as between task avoidance and spelling (e.g., Georgiou et al, 2010;Liao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…7 Birçok çalışmada ÖÖB ile DEHB arasındaki ilişki incelenmiştir. [8][9][10][11][12] Bu çalışmalarda öğrenme güçlüğü çeken çocuklarda dikkat sorunlarının ya da DEHB tanısının daha sık olduğu gözlenmiştir. ÖÖB olan çocuklarda tüm içe atım ve dışa atım bozukluklarının belirtileri daha sık görülmekle birlikte, ÖÖB ve DEHB'nin birlikte görüldüğü hastalarda psikopatoloji daha yoğun seyretmektedir.…”
Section: Introductionunclassified
“…In this article, we continue to report on our International Longitudinal Twin Study (ILTS) of early language and literacy development (Byrne et al 2002;Byrne et al 2005;Byrne et al 2006;Byrne et al 2007;Samuelsson et al 2007;Willcutt et al 2007). The main purpose here was to compare genetic and environmental influences on early reading and spelling skills across three twin samples tested in the United States, Australia, and Scandinavia (i.e., Sweden and Norway) and across time of testing (i.e., kindergarten and Grade 1).…”
mentioning
confidence: 99%